A novel comparison between standard and new testing procedures to assess shock absorbency of third generation artificial turfs - Nunome, H.; Inoue, K.; Shinkai, H.; Kozakai, R.; Suito, H.; Ikegami, Y. (Sports Engineering, 2014)
This study aims to re-examine to what extent the testing procedure of the Artificial Athlete Berlin (DIN18032) is a valid evaluation method to assess the shock absorbency of third generation artificial turf (3-g turf) and to establish a new testing procedure, which precisely reflects the acute load by human sports action. The DIN test was conducted for 3-g turfs with different infill component. The baseline of the load of acute human sports action was obtained from the ground reaction force underneath the standard type of 3-g turf sample during landing from a 55-cm height with minimal shock attenuation. For reproducing the force similar to such a hard landing, a testing rig was developed and the same 3-g turf samples were tested. The DIN test failed to distinguish most types of 3-g turf and was found to be inappropriate to evaluate the shock absorbency of the 3-g turf mainly due to bouncing actions of the test foot on measured samples. In contrast, the newly developed testing rig succeeded in illustrating the differences of shock attenuation properties among most types of 3-g turfs in a high loading condition. In terms of players` safety, the necessity of high loading test using an alternative testing procedure was highlighted.